The Names of Camels and Their Descriptions In (Majma’ Al-Athmal) By Al-Maydani - A Lexical Study According To The Theory Of Semantic Fields - Alshmrani, Mona (Journal of Umm Al-Qura University for Language Sciences and Literature, 2024)
This study aims to explain the impact of cultural heritage on the Arabic language, from the point of view of modern linguistics, in the abundance of camel vocabulary in the book “Majma’ al-Athmal” by Al-Maydani, and this is through studying the significance of the names of camels and their attributes in dictionaries, and in the context of proverbs. The research adopts the descriptive approach with monitoring and analysis tools. The research included an introduction, a preface, a section with two topics, and a conclusion that included a num-ber of results, including: The Arabs’ large vocabulary of camels is due to the depth of the heritage and cultural influence on the language, and the Arabs’ commitment to their cultural heritage set boundaries that required their language not to be affected by other languages. The study recommends the necessity of preserving the heritage and culture of Arab society through studying the linguistic dictionary that represents the true cultural field, and researchers should pay attention to the words that society has given value, such as horse, desert, fire.